PENGEMBANGAN PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN BERBASIS NILAI UNTUK MENUMBUHKAN KARAKTER KEBANGSAAN SISWA SEKOLAH DASAR - Mulyadi Mulyadi; Saparuddin Saparuddin; Nur Indah Pratiwi; Abdul Wahid; Nur Afni (Universitas Borneo Tarakan, 2026)
This study aims to examine how values foster the national character of elementary school students. National character education is a crucial aspect in fostering nationalism, responsibility, tolerance, and love of the homeland from an early age. This research method involves examining and analyzing various research findings, books, and library research documents. The study's findings indicate that values-based civic education can be integrated through a contextual approach, role modeling, habituation, and the use of active and participatory learning methods. Developing learning that emphasizes Pancasila values has been shown to enhance students' understanding and internalization of national character. Therefore, values-based civic education plays a strategic role in shaping a young generation with character, noble personalities, and a strong sense of national awareness.